2017
DOI: 10.11648/j.ijsedu.20170505.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Attitude Towards Mathematics on Achievement of Grade 10 and 12 Female Students in Comparison with Their Male Counterparts: Wolkite, Ethiopia

Abstract: Exploring why more males achieve more than females in mathematics at secondary school level when there appear to be no gender differences in the achievement at earlier years is worthy of investigation. The aim of this study was to investigate the influence of attitude towards mathematics on the achievement of female students in comparison with their male counterparts and also to examine the relationship between attitudes and mathematics achievement. The participants of the study were 240 grade ten and 127 grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In conclusion, when the overall t-test was conducted for all the constructs there was statistically significant difference among the groups in their attitude towards geometry in favour of the male PSTs. This study is similar to Asante (2012), Michelli (2013), Sunzuma et al (2013), Simegn andAsfaw (2018), andTasdemir (2009) where they all found that, male students have more positive attitude than their female counterparts. The findings of this study differ from that of Awofala (2016) discloses that there was no significant difference by gender, selfconfidence, enjoyment, motivation, and value of mathematics.…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, when the overall t-test was conducted for all the constructs there was statistically significant difference among the groups in their attitude towards geometry in favour of the male PSTs. This study is similar to Asante (2012), Michelli (2013), Sunzuma et al (2013), Simegn andAsfaw (2018), andTasdemir (2009) where they all found that, male students have more positive attitude than their female counterparts. The findings of this study differ from that of Awofala (2016) discloses that there was no significant difference by gender, selfconfidence, enjoyment, motivation, and value of mathematics.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…It also revealed that teachers' positive attitude radiated confidence in students, hence made them develop positive attitude towards the learning of geometry. Simegn and Asfaw (2018) study used a sample of 367 comprising of 240 grade 10 students and 127 grade 12, with stratified random sampling technique. The aim of their study examined the effect of students' attitude towards geometry on the achievement of female and their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In Wolkite Town, 240 students were surveyed using Attitude Towards Mathematics Scales (ATMS), which consists of five components, namely, Value, Male Domain, Enjoyment, Motivation and Confidence. The study found that mathematics attitude had the strongest positive significant correlation on mathematics achievement (Simegn & Asfaw, 2018). Kandemir and Akbaş-Perkmen (2017) found that mastery experience, a source in mathematics self-efficacy, has a significant and positive influence on mathematics achievements.…”
Section: Success Indicators Of Mathematical Problem-solving Performancementioning
confidence: 94%
“…Students' feeling of pleasure in solving challenging mathematics problems, willingness to participate in mathematics discussion and excitement in the mathematics classroom (Simegn et al, 2018).…”
Section: Enjoymentmentioning
confidence: 99%
“…In other words, when students hold favorable attitudes toward math-related tasks, they are more likely to engage in those targeted tasks and tend to put more effort into completing their work with high quality, which contributes to positive behavioral outcomes (e.g., performing better on math tests and/or earning higher grades in math courses). Consequently, numerous studies have examined the effects of various components of math attitudes (e.g., enjoyment/liking, motivation, self-confidence, and perceived value) on math achievement (e.g., Khine, Al-Mutawah, & Afari, 2015;Simegn & Asfaw, 2018) to provide a more comprehensive picture of math learning processes. However, subscales of math attitudes should be validated as reliable measurements for assessing math attitudes.…”
Section: Introductionmentioning
confidence: 99%